Assisting the automated analysis of chemical-Analytical measurements in spirits using validated algorithms and an intuitive user interface - Grasskamp, Andreas T.; Singh, Satnam; Haug, Helen; Sauerwald, Tilman (Journal of Sensors and Sensor Systems, 2023)
Exhaustive analysis of chemical measurements requires considerable expenditure of time and personnel. However, many aspects of this can be automated by translating manual work into objective algorithmic routines. To this end, we developed adaptable software for gas chromatography data and validated analysis steps using whisky samples. We employed an unspecific, larger, in-house volatile organic compound (VOC) database and another specifically curated database of 217 known whisky chemicals, to automate database-matching based on mass spectra and retention indices. We managed to reduce the amount of necessary interaction, facilitated complex analysis for the less experienced user, and showed that characteristic whisky components constituted the majority of detected molecules in all 16 analyzed samples. With this approach, we present a decisive contribution towards the automated assessment of aroma profiles in food.
CRIS-Team Scopus Importer:2023-04-14